1996
DOI: 10.1063/1.116129
|View full text |Cite
|
Sign up to set email alerts
|

White light emission from a polymer blend light emitting diode

Abstract: A new type of polymer light emitting diodes that emit white light is reported. In these diodes, several electroluminescent substituted polythiophenes have been combined to give the necessary components of the visible spectrum. These emitting polymers are then mixed with an insulating polymer to diminish the energy transfer from high-band-gap polymers to low-band-gap polymers. The resulting emission at 20 V is shown to be close to the equienergy white point as defined by the CIE (Commission Internationale de l’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
150
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(153 citation statements)
references
References 0 publications
2
150
0
1
Order By: Relevance
“…Single layer devices are more attractive due to its ease of fabrication, large scale production and cost effective features, and according to published data they are more stable than those built with emitters in separated layers [20,[29][30][31]. Therefore, for a system where the emission of one material spectrally overlaps with the absorption of another, a separating material had to be incorporated into the blend so as to prevent complete energy transfer and to give white emission with a wide spectral range [32]. To achieve this goal, morphology control of the polymer film is a crucial step and plays a main role on the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Single layer devices are more attractive due to its ease of fabrication, large scale production and cost effective features, and according to published data they are more stable than those built with emitters in separated layers [20,[29][30][31]. Therefore, for a system where the emission of one material spectrally overlaps with the absorption of another, a separating material had to be incorporated into the blend so as to prevent complete energy transfer and to give white emission with a wide spectral range [32]. To achieve this goal, morphology control of the polymer film is a crucial step and plays a main role on the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] These properties could be very important for example when trying to achieve white emission, one of the most important developments in the field of polymer emitting devices, where complex mixtures are used in order to gain broad white emission and balanced electron and hole transport within a single "emission" layer. [8,9,10,11] Polyfluorenes have been extensively studied for display applications, owing to their pure blue and efficient electroluminescence coupled with a high charge carrier mobility and good processability. [12] Several studies have been reported, including mixing of polyfluorenes with different emissive materials and applying them in single or multiple layers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed by Siemens in Germany, white LEDs offer a long-lasting (hundreds of thousands of hours) light source that is very power efficient [6]- [8]. The efficiency is critical in the solar lantern, since the objective is to provide light for long periods of time using only a battery.…”
Section: A White Ledsmentioning
confidence: 99%